Fixed Point Theorems for Generalized Mizoguchi-Takahashi Graphic Contractions. (31st July 2016) - Hussain, Nawab; Ahmad, Jamshaid; Kutbi, Marwan Amin
Abstract : Remarkable feature of contractions is associated with the concept Mizoguchi-Takahashi function. For the purpose of extension and modification of classical ideas related with Mizoguchi-Takahashi contraction, we define generalized Mizoguchi-Takahashi G -contractions and establish some generalized fixed point theorems regarding these contractions in this paper. Some applications to the construction of a fixed point of multivalued mappings in ε -chainable metric space are also discussed.